Anti-neutrophil cytoplasmic antibodies associated vasculitis with interstitial lung disease: a case report - Taneja, Vinus; Khosla, Pooja; Dessai, Rishikesh (International Journal of Research in Medical Sciences, 2024)
Anti-neutrophil cytoplasmic antibodies (ANCA) associated vasculitis is a necrotizing vasculitis that primarily affect small blood vessels of the airway and kidneys. The major clinicopathologic feature include microscopic polyangiitis and granulomatosis with polyangiitis. There are several studies done that have shown the association of interstitial lung disease (ILD) and ANCA vasculitis. Majority of the studies showed that the prognosis was bad in patients with AAV and ILD, then those without it, and patients with pulmonary fibrosis and ANCA had as low a prognosis as patients with IPF without ANCA. We hereby report a case of a female patient in her 70s who was been treated as a case of infection at different hospital, only to be diagnosed later as ANCA associated vasculitis with interstitial lung disease. Methylenetetrahydrofolate reductase (MTHFR) enzyme is one of the key enzymes involved in the metabolism of folate.